The development of the AUMDROID application (an android-based problem expression tool) - Kaihatu, Jovial; Aryani, Farida; Sinring, Abdulah (Program Studi bimbingan Konseling PPs UNM Makassar, 2024)
This study aims to investigate the needs, produce a prototype, and determine the validity and practicality of the AUMDROID application for students of SMKN (State Vocational High School) 10 Makassar. The respondents were six school counselors and twenty-five eleventh-grade TELI 1 students. A research and development (R&D) framework was adopted to conducted this study. Observations, interviews, as well as validity and product testing questionnaires were performed to collect the data. Descriptive quantitative analysis was performed to analyze the data. Results showed that the AUMDROID application was needed at SMKN 10 Makassar to facilitate and streamline the processes of guidance and counseling assessment, as well as the needs analysis of problems faced by students. The prototype of the AUMDROID application was developed by designing the Problem Expression Tool (AUM) based on the Student Independence Competency Standards (SKKPD) and developmental tasks. The developed AUMDROID application is valid and feasible for use at SMKN 10 Makassar. The AUMDROID application is practical due to its convenience and accessibility at all times and in any location